Protective effects of Cordyceps militaris against hepatocyte apoptosis and liver fibrosis induced by high palmitic acid diet - Tsai, Wan-Ting; Situmorang, Jiro Hasegawa; Kuo, Wei-Wen; Kuo, Chia-Hua; Lin, Shinn-Zong; Huang, Chih-Yang; Ho, Tsung-Jung (Frontiers in Pharmacology, 2025)
BackgroundFatty Liver Disease (FLD) progresses from steatosis to steatohepatitis and, if left untreated, can lead to irreversible conditions such as cirrhosis and hepatocarcinoma. The etiology of FLD remains unclear, but factors such as overconsumption, poor diet, obesity, and diabetes contribute to its development. Palmitic acid (PA) plays a significant role in FLD progression by inducing apoptosis, inflammation, oxidative stress, and endoplasmic reticulum (ER) stress in hepatocytes. Cordyceps militaris (CM), a fungus with various biological activities, including antioxidant properties is examined both in vitro and in vivo to assess its effectiveness in mitigating PA-induced hepatocyte apoptosis and preventing FLD progression.PurposeThis study aims to investigate the potential and mechanism of CM in combating FLD, particularly in inhibiting hepatocyte apoptosis.MethodsIn vitro studies utilized Clone9 hepatocytes treated with PA to simulate FLD conditions. The effects of CM ethyl acetate extract (EAECM) on apoptosis, mitochondrial function, ER stress, inflammation, and oxidative stress were evaluated. In vivo experiments involved FVB mice fed a NASH diet containing high levels of PA to induce FLD, with powdered CM administered orally to assess its impact on body weight, fasting blood glucose level, liver health, fibrosis, and markers of ER stress, inflammation, and oxidative stress.ResultsEAECM demonstrated protective effects against PA-induced apoptosis, mitochondrial dysfunction, ER stress, inflammation, and oxidative stress in vitro. In vivo, powdered CM supplementation attenuated body weight gain, improved fasting blood glucose level, prevented hepatomegaly, reduced serum triglycerides, and inhibited liver fibrosis. Furthermore, powdered CM treatment mitigated ER stress, inflammation, and oxidative stress in the liver of mice receiving a NASH diet.ConclusionC. militaris holds promise as a therapeutic agent for FLD, as evidenced by its ability to alleviate PA-induced hepatocytes damage and hinder FLD progression in mice. Further research is warranted to identify the active compounds responsible for its beneficial effects and to explore its potential clinical applications in treating FLD.